Guidelines of the International Headache Society for controlled trials of preventive treatment of migraine attacks in episodic migraine in adults - Diener, Hans-Christoph; Tassorelli, Cristina; Dodick, David W; Silberstein, Stephan D; Lipton, Richard B; Ashina, Messoud; Becker, Werner J; Ferrari, Michel D; Goadsby, Peter J; Pozo-Rosich, Patricia; Wang, Shuu-Jiun; Houle, Timothy T; et al. (Cephalalgia, 2020)
Clinical trials are a key component of the evidence base for the treatment of headache disorders. In 1991, the International Headache Society Clinical Trials Standing Committee developed and published the first edition of the Guidelines for Controlled Trials of Drugs in Migraine. Advances in drugs, devices, and biologicals, as well as novel trial designs, have prompted several updates over the nearly 30 years since, including most recently the Guidelines for controlled trials of preventive treatment of chronic migraine (2018), the Guidelines for controlled trials of acute treatment of migraine attacks in adults (2019), and Guidelines for controlled trials of preventive treatment of migraine in children and adolescents (2019). The present update incorporates findings from new research and is intended to optimize the design of controlled trials of preventive pharmacological treatment of episodic migraine in adults. A guideline for clinical trials with devices will be published separately.